ECHINODERM COMMUNITY STRUCTURE IN TAMBA BEACH, NORTH MINAHASA REGENCY, NORTH SULAWESI PROVINCE - Jelita Pricilya Tompolumiu; Verawati Ida Yani Roring; Nova Laurin Isye Mourein Ogi; Nonny Manampiring (Universitas Negeri Manado, 2023)
Tamba Beach has several ecosystems, namely seagrass beds, sandy and rocky. Ecologically, seagrass beds are home to marine life, including Echinodermata. Echinoderms play an important role as an integral part of the food chain, eating organic waste. The purpose of this study was to analyze the community structure of Echinoderms at Station I (Seagrass Zone), Station II (Sandy Zone) and Station III (Coral Zone). Two methods are used in this study. The first is a qualitative description method by directly observing and quantitatively calculating the diversity index, uniformity index, dominance and abundance index formulas. The echinoderms found consisted of 4 classes, namely Holothuidea, Ophiuroidea, Echinoidea and class Asteroidea. The echinoderms found at the study site used a diversity index classified as stable. The dominance index is low because there are no dominant individuals, and the uniformity index is low. From the results obtained from the abundance in Tamba Beach, the highest value was in the Diadema setosum species with 113 individuals. Diadema setosum has the highest quantity at the three existing stations. This species can adapt to environmental changes.